Matching final year project topics with students using stable marriage model / Naimah Mohd Hussin and Ammar Azlan - Mohd Hussin, Naimah; Azlan, Ammar (UiTM Cawangan Perlis, 2017)
Every semester, a new batch of final year students needs to find a topic and a supervisor to complete their final year project requirement. The problem with the current approach is that it is based on first come first serve. So, the pairing between student and supervisor is not the optimal ones, i.e. some students may not get their preferred topic or supervisor. Plus, it is also time consuming for both students and supervisors. The researcher is motivated to solve this long overdue problem by applying a stable marriage model that is introduced by Gale and Shapley hence the name Gale-Shapley Algorithm. To determine the functionality of this approach, a system prototype has been constructed and a random dataset is used. The result, 60% of the students get their first choice topics while the remaining students get their second or third choice. This is a remarkable outcome considering the time and effort saved compared to the current process. Therefore, stable marriage model is applicable in solving student - topic pairing.